Anticoagulant Properties of Medicinal Plants of Asteraceae: A Systematic Review - Alcantara, Samantha Ysabelle; Jr., Romulo R. Macadangdang; Ciocson, Kyla Stephanie; Escabusa, Charilyn; Llamas, Danica Mei; Rivera, Justin Romel; Santos, Stefhanie (Asian Journal of Biological and Life Sciences)
The Asteraceae family is considered to be the largest family of flowering plants. Asteraceae includes annuals, perennials, ground covers, vines, and shrubs. Plants belonging to this family are used as a conventional medicine all over the world, and it has been shown to have a range of biological benefits, including anti-inflammatory, antioxidant, and anticoagulant properties. Plants from the Asteraceae are believed to be rich in flavonoids, coumarins, and other constituents that help in the coagulation process. This systematic review generally aims to provide an overview concerning the anticoagulant activity of different medicinal plants under the family of Asteraceae. After rigorous screening using combined SPIDER and PICO strategies, 17 experimental studies with Asteraceae plants showing anticoagulant activity were included. The different plants from the family were extracted using water, methanol, ethanol, and hexane method. Anticoagulant activity of different plants from the Asteraceae family was determined by performing tests and monitoring activated partial thromboplastin time and prothrombin time in vitro and in vivo to assess the intrinsic and extrinsic pathway. Moreover, the presence of coumarin, flavonoids, and polysaccharides significantly increased the aPTT and PT. Thus, these results suggest that the chemical constituents of Asteraceae plants may have the potential to prevent or improve thrombosis by inhibiting platelet activation and blood coagulation.
Keywords: Activated partial thromboplastin time; Anticoagulant activity; Asteraceae; Phytochemical; Prothrombin time